Detection of tumors with fluoromarker‐releasing bacteria. Issue 1 (20th June 2019) - Panteli, Jan T.; Van Dessel, Nele; Forbes, Neil S.
Abstract : Combining the specificity of tumor‐targeting bacteria with the sensitivity of biomarker detection would create a screening method able to detect small tumors and metastases. To create this system, we genetically modified an attenuated strain of Salmonella enterica to release a recombinant fluorescent biomarker (or fluoromarker). Salmonella expressing ZsGreen were intravenously administered to tumor‐bearing mice and fluoromarker production was induced after 48 hr. The quantities and locations of bacteria and ZsGreen were measured in tumors, livers and spleens by immunofluorescence, and the plasma concentration of ZsGreen was measured using single‐layer ELISA. In the plasma, the ZsGreen concentration was in the range of 0.5–1.5 ng/ml and was dependent on tumor mass (with a proportion of 0.81 ± 0.32 ng·ml −1 ·g −1 ). No adverse reaction to ZsGreen or bacteria was observed in any mice. ZsGreen was released at an average rate of 4.3 fg·CFU −1 ·hr −1 and cleared from the plasma with a rate constant of 0.259 hr −1 . ZsGreen production was highest in viable tissue (7.6 fg·CFU −1 ·hr −1 ) and lowest in necrotic tissue (0.47 fg·CFU −1 ·hr −1 ). The mass transfer rate constant from tumor to blood was 0.0125 hr −1 . Based on these measurements, this system has the capability to detect tumors as small as 0.12 g. These results demonstrate four essential mechanisms of this method: ( i ) preferential tumor colonization by bacteria, ( ii ) fluoromarker release in vivo, ( iii ) fluoromarker transport through tumor tissue and ( iv ) slow enough systemic clearance to enable measurement. This bacteria‐based blood test would be minimally invasive and has the potential to identify previously undetectable microscopic tumors. Abstract : What's new? Facultative anaerobic bacteria readily colonize solid tumors. The diffusion into the bloodstream of a fluorescent marker released by these organisms as they proliferate inside a tumor could facilitate cancer detection. Here, an engineered bacterial system employing a fluoromarker‐producing attenuated strain of Salmonella enterica demonstrated capability in detecting tumor volumes of 0.12 grams in mice. This tumor size is comparable to the smallest tumors detected by tomographic imaging. The experiments provide insight into mechanisms underlying bacterial tumor colonization, fluoromarker release in vivo, and fluoromarker transport through tumor tissue. Fluoromarker tissue transport and systemic clearance was gradual, enabling measurement in blood plasma.